Evaluating the Impact of Collaborative Art, Therapy and Training on Police Legitimacy: The Perceptions Held by Individuals with Substance Abuse Disorder and Police Officers - Williams Jr., Frederick A.; Higgins, George E. (International Journal of Criminology and Sociology, 2024)
This qualitative pilot study was funded by a federal micro-grant to seek to fill a void in the literature on police legitimacy. The focus of this pilot study was to determine if collaborative art therapy and training can change the perceptions of police legitimacy held by individuals with substance use disorder (SUD) or the perceptions of the police toward individuals with SUD. Besides the collaborative activities, individuals with SUD and police officers were provided with therapy and/or training sessions during the period of collaboration. The methodology for this study included the use of electronic survey instruments to evaluate any changes in perception. These instruments were administered anonymously before and after all therapy, training, and collaboration activities occurred. Each instrument contained open-ended questions relating to Police Legitimacy Scale (PLS) (Tankebe et al., 2016) categories, as well as additional measures. Analysis included qualitative methods to provide context and identify themes for content analysis. Findings did not confirm change overall however, positive responses support police legitimacy, perceptual changes and relationship building. Recommendations are made for relationship building through increased interaction, excluding enforcement activities between individuals with SUD and the police using collaborative projects such as art therapy.